Estudo do perfil oxidativo e avaliação de parâmetros enzimáticos em pacientes com câncer de próstata - Battisti, Vanessa (2012)
Prostate cancer is recognized as one of the most important medical problems in the male population. Inherent or acquired alterations in cellular metabolism that occur over the years may be involved in the process of developing this cancer. Thus, oxidative stress may play an important role in cellular processes associated with the initiation and development of prostate cancer. On the other hand, the cancer may be associated with changes in platelet aggregation and metabolism of nucleotides. In addition, enzymes that degrade esters of choline are well known as participating in non-cholinergic functions and intervene in important cell processes such as proliferation, differentiation and apoptosis. Considering such statements, this study aimed to evaluate the oxidative profile, through the determination of parameters such as the TBARS and protein carbonyl content and antioxidant defenses, by determine the catalase (CAT) and superoxide dismutase (SOD) activity and non-protein thiols, vitamin C and vitamin E levels. Also, determine ectonucleotidases enzyme activities represented by the enzymes NTPDase, E-NPP, 5'nucleotidase and adenosine deaminase (ADA) and verified the acetylcholinesterase (AChE) and butyrylcholinesterase (BuChE) activities. In addition, we evaluated the influence of Gleason score, the presence or absence of metastasis and type of treatment used by patients in the parameters analyzed. The results show that the content of TBARS and protein carbonylation levels increased in patients when compared with the control group. In addition, changes in the antioxidant defenses were observed. The CAT activity was decreased and SOD activity increased in patients compared to controls. We found also an increase in the levels of non-protein thiols in plasma and erythrocytes and a decrease in serum levels of vitamin C and vitamin E in patients. These results suggest an increased formation of reactive species and an imbalance in the enzymatic and non-enzymatic antioxidant system defense in patients with prostate cancer. Moreover, it was observed that advanced prostate cancer is associated with a state of high oxidative stress. The results showed that nucleotides hydrolysis (ATP, ADP and AMP) were increased in patients compared to controls, which maybe observed by the increase in the enzymes activity (NTPDase, E-NPP and 5'Nucleotidase). On the other hand, our results showed a decrease in ADA activity in serum of these patients. These results reflect the increase in the nucleotide hydrolysis and the consequent increase in the adenosine concentrations that may be envolved in the tumorigenesis process. Our results also showed that inhibition of platelet aggregation was decreased only in patients with prostate cancer before starting treatment. The AChE and BuChE activities were decreased in patients in relation to the control group. The decrease in the cholinesterases activities and the consequently increase in acetylcholine levels suggest the participation of this molecule in the process of cancer development. Finally, changes in the NTPDase, 5' nucleotidase, E-NPP, ADA, AChE and BuChE activities when patients were divided in groups considering the Gleason score, presence or absence of bone metastasis and the treatment, indicate that these parameters must be considered.